Socio-economic characteristics of dairy and non-dairy households of chars of Northern Bangladesh (Bangladesh Veterinarian, 2018)
Dairy and non-dairy households in chars in northern Bangladesh were compared. About 35% of dairy households earned money by selling milk along with labour. Dairy households owned more land than the non-dairy group. More dairy households (70%) had drinking water and 74% had sanitation facilities, while 49% and 44% non-dairy households had such facilities. The dairy households owned 3065 livestock, of which 946 were cattle; while non-dairy households owned 1915 livestock, including 17 cattle. Average daily income of each dairy household was 129 Taka (US$ 1 = Taka: 56.31), and for non-dairy household it was 109 Taka. Many dairy households had a bicycle (n = 54), radio (n = 59) and cell phone (n = 211), but fewer in the non-dairy had a bicycle (n = 8) and cell phone (n = 43). The livestock are living assets for the flood-prone households and source of daily income.Bangl. vet. 2017. Vol. 34, No. 2, 52-60